2022
DOI: 10.1002/jdd.12909
|View full text |Cite
|
Sign up to set email alerts
|

Students’ and tutors’ perceptions of a deliberate simulated practice using patient‐specific virtual and three‐dimensional printed teeth models: A pilot study

Abstract: Objective This pilot study aimed to investigate the perceptions of dental students and their tutors of a deliberate simulated practice using patient‐specific virtual and three‐dimensional (3D) printed teeth models. This is before they perform their first indirect posterior tooth restoration on their patients. Methods Seventy‐eight fourth‐year dental students from the 2021 Comprehensive Clinic I course at the University of the Andes, Chile, were invited to participate in a deliberate practice protocol. This con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Likewise, another pilot protocol is being implemented to allow the students to practice their patients' clinical procedures beforehand, by using virtual and 3D-printed models mounted on phantom heads. 35 We believe that these and other interventions during and after the preclinical-toclinical transition will improve the learning environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, another pilot protocol is being implemented to allow the students to practice their patients' clinical procedures beforehand, by using virtual and 3D-printed models mounted on phantom heads. 35 We believe that these and other interventions during and after the preclinical-toclinical transition will improve the learning environment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have initiated a pilot programme for third‐year students within their semiology course, consisting of simulated patients that have been especially designed to foster students' communication skills. Likewise, another pilot protocol is being implemented to allow the students to practice their patients' clinical procedures beforehand, by using virtual and 3D‐printed models mounted on phantom heads 35 . We believe that these and other interventions during and after the preclinical‐to‐clinical transition will improve the learning environment.…”
Section: Discussionmentioning
confidence: 99%
“…1 Multiple published studies have demonstrated the value of three-dimensional (3D) printed teeth for dental education. [2][3][4][5] A limitation common to these publications has been the inability to 3D print using multiple materials simultaneously. 3 One strategy for creating a multi-material tooth was to create a tooth with a hollow pulp chamber and cavity preparation that was later filled with impression material and resin composite, respectively.…”
Section: Problemmentioning
confidence: 99%
“…Extracted human teeth have traditionally been used to train dental students which have come under increased scrutiny in recent years 1 . Multiple published studies have demonstrated the value of three‐dimensional (3D) printed teeth for dental education 2–5 . A limitation common to these publications has been the inability to 3D print using multiple materials simultaneously 3 .…”
Section: Problemmentioning
confidence: 99%
“…Collaboration between several dental schools around the world and various engineering and flight simulation companies pushed the engineering and content development required to achieve the current level of VR haptic dental simulation, while also enabling large‐scale production of VR dental trainers. Considering the challenge of generating scientific evidence while developing and implementing this new technology in dental curricula, different aspects of VR dental training were built and validated 14–17 : the creation of VR models based on real teeth with and without pathology, 9,18 testing FF and its effect on users' performance and training experience, 19–23 assessing transferability of skills to reality 24,25 and ultimately, developing and assessing the educational value of simulating real patients' clinical situations in VR 26–28 . Regardless of the growing body of validating evidence, including evidence showing at least comparable results when used instead of analogue simulation (mannequins), 29,30 the paradigm of traditional dental training with mannequins and resin or extracted teeth has proven to be deeply rooted, and schools have struggled with acceptance from faculty and students while trying to implement VR haptic dental training.…”
Section: Introductionmentioning
confidence: 99%